Mixed matrix membrane as well as preparation method and application thereof
By loading MA composite amine on MOF materials, the composite amine coordination introduces functional groups that can react with CO2, which solves the problems of low permeability and low selectivity in the existing membrane separation technology, and achieves efficient CO2 separation, which is suitable for large-scale industrial applications.
Patent Information
- Application Number
- CN202311432417.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-31
AI Technical Summary
In the existing membrane separation technology, the separation membrane material has low permeability and low selectivity, resulting in low CO2 separation efficiency and difficulty in achieving large-scale industrial applications.
Using a new high-efficiency MOF mixed matrix membrane based on MA composite amine coordination, the MA composite amine is loaded on the MOF material, and the functional groups that can undergo a reversible chemical reaction with CO2 are introduced using the composite amine coordination to enhance the transmission of CO2 in the membrane.
A hybrid matrix membrane with both high selectivity and high permeability is achieved, breaking through the "trade-off" effect, suitable for large-scale continuous preparation, and improving the CO2 separation efficiency.
Smart Images

Figure BDA0004524021750000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of membrane separation, and in particular to a mixed matrix membrane and a preparation method and application thereof. Background Art
[0002] The main carbon dioxide capture technologies include absorption, adsorption, membrane and cryogenic separation. Among them, membrane separation carbon dioxide capture technology has attracted extensive attention from researchers. The membrane separation method has simple process, small equipment investment, low energy consumption, flexible operation and small footprint, and has broad application prospects in flue gas CO2 capture. In recent years, the United States, Germany, Norway and other countries have actively carried out research on membrane technology for flue gas CO2 capture.
[0003] The goal of the CO2 capture process from combustion tail gas is that the purity of the captured CO2 should be greater than 95vol%, the recovery rate should be greater than 90%, and the increase in the power generation cost of the power plant should not exceed 35%. At present, the membrane technology used to capture CO2 in the flue gas of power plants is still difficult to meet the technical and economic requirements of industrial applications. This is related to many factors, such as the CO2 / N2 separation performance of the membrane, the design of the membrane assembly and the membrane process technology. The existing commercial CO2 separation membranes are all polymer membranes with a CO2 permeation rate of 50-100GPU and a CO2 / N2 separation factor of 20-30. In order to accelerate the industrialization process of membrane technology for capturing CO2 from flue gas, many scientific research institutions and companies at home and abroad have developed a variety of high-performance CO2 separation membranes and membrane process technologies. The Membrane Technology Research Center (MTR) of the United States and the GKSS Research Center of Germany used polyethylene oxide polymer membrane materials to prepare PolarisTM (CO2 permeation rate reaches 1000-2000GPU, CO2 / N2 separation factor is about 50) and Polyactive flat composite membrane (CO2 permeation rate is close to 1000GPU, CO2 / N2 separation factor is about 55). MTR used the PolarisTM flat composite membrane prepared on a large scale to conduct a pilot scale (1 ton / day) test study on capturing CO2 in flue gas at the National Carbon Capture Research Center of the United States. Research institutions such as Ohio State University and the Norwegian University of Science and Technology have developed a series of CO2 separation membranes containing functional groups using polymer membrane materials rich in functional groups such as amine groups, such as polyvinylamine (PVAm), polyethyleneimine (PEI) and polyallylamine (PAAm), and prepared flat membrane modules and hollow fiber membrane modules, respectively, and conducted real flue gas tests.
[0004] Environmentally friendly, energy-saving and efficient membrane separation technology is the focus of current gas separation technology research. In the current research and development of membrane materials, MOF mixed matrix membranes have attracted extensive attention from researchers because of their unique advantages. At present, a large number of MOF mixed matrix membrane studies have been reported. In order to further obtain high-performance membrane materials, it is very effective to modify MOF materials. The chemical modification process is difficult to control, and the original MOF material properties are easily destroyed during the modification process. Compared with the chemical modification method, other functional materials are combined with MOF materials to prepare composite materials. By designing a suitable composite method, the advantages of two materials can be maximized, so that novel functionalized MOF composite materials can be obtained according to specific applications. Functionalized MOF composite materials are used as additives to prepare mixed matrix membranes to obtain novel membrane materials.
[0005] The present invention takes improving the separation performance of CO2 separation membrane as a starting point, and provides a novel high-efficiency MOF mixed matrix membrane based on MA complex amine coordination and a preparation method thereof. Summary of the invention
[0006] The purpose of the present invention is to overcome the technical problem that the CO2 separation efficiency is low due to the low permeability and low selectivity of the separation membrane materials in the existing membrane separation technology, which makes it difficult to achieve large-scale industrial application of the CO2 capture technology by membrane separation, and to provide a mixed matrix membrane and its preparation method and application. The mixed matrix membrane of the present invention has both high selectivity and high permeability and is suitable for large-scale continuous preparation.
[0007] In order to achieve the above-mentioned object, the present invention provides a mixed matrix membrane in a first aspect, the mixed matrix membrane comprising a polymer matrix and a filler dispersed in the polymer matrix;
[0008] The filler comprises a MOF material and a MA complex amine loaded on the MOF material;
[0009] The MA complex amine is selected from one or more of ethanolamine (MEA), methyl monoethanolamine (MMEA), diethanolamine (DEA), N-methyldiethanolamine (MDEA), diisopropylamine (DIPA), hydroxyethylethylenediamine (AEEA) and 2-amino-2-methyl-1-propanol (AMP).
[0010] A second aspect of the present invention provides a method for preparing the mixed matrix membrane of the present invention, the method comprising:
[0011] The polymer matrix and filler are dispersed in an organic solvent according to a certain proportion to obtain a membrane-forming liquid, and then the organic solvent in the membrane-forming liquid is removed and dried to obtain a mixed matrix membrane.
[0012] The third aspect of the present invention provides an application of the mixed matrix membrane described in the present invention in CO2 membrane separation.
[0013] Through the above technical scheme, the filler of the present invention exists in the membrane as a dispersed phase, and the polymer matrix material is composed of a continuous phase polymer; the filler includes MOF material and MA complex amine loaded on the MOF material, and the MA complex amine coordinates with the metal in the MOFs material through the complex amine coordination effect, introduces functional groups that can undergo reversible chemical reactions with CO2 into the membrane, and strengthens the transfer of CO2 in the membrane, thereby breaking through the "trade-off" effect and obtaining a promoted transfer membrane with both high permeability and high selectivity. DETAILED DESCRIPTION
[0014] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0015] A first aspect of the present invention provides a mixed matrix membrane, the mixed matrix membrane comprising a polymer matrix and a filler dispersed in the polymer matrix;
[0016] The filler comprises a MOF material and a MA complex amine loaded on the MOF material;
[0017] The MA complex amine is selected from one or more of ethanolamine (MEA), methyl monoethanolamine (MMEA), diethanolamine (DEA), N-methyldiethanolamine (MDEA), diisopropylamine (DIPA), hydroxyethylethylenediamine (AEEA) and 2-amino-2-methyl-1-propanol (AMP).
[0018] The mixed matrix membrane uses a polymer matrix material as a continuous phase to form a membrane, and uses a loaded MA complex amine MOF material as a filler, which exists as a dispersed phase in the membrane. MOF material is a new type of multi-porous crystalline material formed by self-assembly between inorganic metal clusters and organic ligands, which has a large specific surface area and a regular pore structure, and can effectively enhance the flux of membrane material separation. The MA complex amine coordinates with the metal in the MOFs material through the complex amine coordination, introduces functional groups that can undergo a reversible chemical reaction with CO2 into the membrane, and strengthens the transfer of CO2 in the membrane, breaking through the "trade-off" effect, thereby obtaining a promoted transfer membrane with both high permeability and high selectivity.
[0019] According to a preferred embodiment of the present invention, the mass content of the filler is 3-20 wt % based on the total weight of the mixed matrix membrane.
[0020] According to a preferred embodiment of the present invention, the MOF material comprises:
[0021] Metal center; and
[0022] An organic ligand that hybridizes with a bimetallic center through a coordination bond to form a stereo network structure crystal.
[0023] According to a preferred embodiment of the present invention, the metal is selected from one or more of iron, copper, zinc, titanium, cobalt, nickel and chromium.
[0024] According to a preferred embodiment of the present invention, the organic ligand is selected from one or more of benzimidazole, imidazole-2-carboxaldehyde, 2-methylimidazole, and 2-aminoterephthalic acid.
[0025] In the present invention, there is no particular limitation on the preparation method of the MOF material. For example, the MOF material is prepared by a solvent thermal synthesis method, wherein the reactants are dispersed in a solvent to form a reaction solution, which is then heated to a desired temperature in a hydrothermal reactor to react and synthesize.
[0026] According to a preferred embodiment of the present invention, the MOF material is selected from one or more of NH2-MIL-101(Cr), NH2-MIL-101(Fe), and NH2-MIL-101(Zn).
[0027] The present invention illustratively provides a method for preparing NH2-MIL-101(Cr)MOFs material, comprising: (1) placing 5 mmol, 1500 mg of Cr(NO3)3·9H2O, 5 mmol, 600 mg of NH2-BDC, and 12 mmol, 400 mg of NaOH in 50 mL of deionized water and stirring at room temperature for 15 min.
[0028] (2) The dispersed reaction solution was transferred to a 200 mL polytetrafluoroethylene reactor, and the reactor was placed in an oven. The reaction temperature was raised to 180°C within 1 hour, and then the reaction was carried out at 180°C for 12 hours, and then the temperature was lowered to room temperature for 2 hours.
[0029] (3) The precipitate in the kettle was centrifuged and then washed several times with N,N'-dimethylformamide and ethanol respectively to remove the unreacted residues in the MOF pores. The product was dried in an oven and finally placed in a vacuum oven at 180°C for further activation treatment to obtain a dry MOF material product NH2-MIL-101(Cr).
[0030] According to a preferred embodiment of the present invention, in the filler, the mass ratio of MA complex amine to MOF material is 0.5-1:0.8-2, preferably 0.8-1:1.
[0031] According to a preferred embodiment of the present invention, the method for preparing the filler comprises:
[0032] The MOF material is contacted with a solution containing MA complex amine, separated, washed and dried.
[0033] The MOF material of the present invention can achieve the purpose of the present invention whether it contains bound water or not. According to a preferred embodiment of the present invention, the MOF material contains bound water.
[0034] According to a preferred embodiment of the present invention, the conditions for removing bound water in the MOF material include: under negative pressure conditions, a temperature of 100-180° C., and a time of 2-24 hours.
[0035] In the present invention, there is no particular limitation on the contact conditions between the MOF material from which bound water is removed and the solution containing the MA complex amine. For example, the temperature can be room temperature (25-30° C.) or heated, preferably room temperature. According to a preferred embodiment of the present invention, the contact time is 3-20 hours.
[0036] According to a preferred embodiment of the present invention, in the solution containing MA complex amine, the solvent is selected from one or more of anhydrous ethanol, anhydrous methanol, and N,N'-dimethylformamide;
[0037] According to a preferred embodiment of the present invention, in the solution containing MA complex amine, the mass ratio of MA complex amine to solvent is 0.2-5:1.
[0038] In the present invention, there is no particular limitation on the type of material of the polymer matrix, and conventional polymer materials in the art can achieve the purpose of the present invention. According to a preferred embodiment of the present invention,
[0039] The polymer matrix is selected from one or more of microporous polymer material PIM-1, cellulose polymer, polysulfone polymer, polyamide polymer, amino polymer, ether oxide polymer, preferably microporous polymer material PIM-1.
[0040] In the present invention, there is no particular limitation on the preparation method of the polymer matrix. The present invention exemplarily provides a preparation method of a microporous polymer material PIM-1. First, 2,2,5,6-tetrafluoroterephthalonitrile (TFTPN) is purified by vacuum sublimation at 120°C to obtain a white crystalline solid; then 2,2,5,6-tetrafluoroterephthalonitrile (TFTPN) is purified by recrystallization in methanol. 35mmol, 8.2g of TFTPN after sublimation treatment, 35mmol, 12.5g of TTSBI after recrystallization in methanol, and 80g, 10.2g of anhydrous K2CO3 are dispersed in 200mL of anhydrous N,N'-dimethylformamide solution. The reaction is carried out under N2 purging conditions, stirring and heating are turned on, the heating temperature is 60°C, and the stirring time is 60h. After the reaction is completed, it is cooled to room temperature, 300mL of deionized water is added, and filtered. The collected product is then dissolved in CHCl3 and precipitated in methanol for purification. The product was then dried at 120 °C under vacuum for 24 h.
[0041] A second aspect of the present invention provides a method for preparing the mixed matrix membrane of the present invention, the method comprising:
[0042] The polymer matrix and filler are dispersed in a first solvent according to a certain proportion to obtain a membrane-forming liquid, and then the organic solvent in the membrane-forming liquid is removed and dried to obtain a mixed matrix membrane.
[0043] In the present invention, there is no particular limitation on the type of the first solvent, as long as it can dissolve the polymer matrix material. According to a preferred embodiment of the present invention, the first solvent is selected from one or more of water, tetrahydrofuran, N.N'-dimethylformamide, methanol, ethanol, dichloromethane, and dimethyl sulfoxide.
[0044] According to a preferred embodiment of the present invention, the total weight of the polymer matrix and the filler accounts for 3-10 wt % of the membrane-forming solution.
[0045] In the present invention, there is no particular limitation on the film-forming method, and conventional film-forming methods in the art can be used in the present invention, such as solution casting, solution casting, coating, spinning, and solvent evaporation.
[0046] According to a preferred embodiment of the present invention, the film forming method is a casting method.
[0047] According to a preferred embodiment of the present invention, in the method for preparing the mixed matrix membrane, the drying conditions include: negative pressure, temperature 60-180° C., and time 12-48 hours.
[0048] A third aspect of the present invention provides an application of the mixed matrix membrane of the present invention in CO2 membrane separation, preferably in CO2 / N2 membrane separation.
[0049] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0050] In order to more clearly explain the present invention, the following embodiments are given, but the present invention can be implemented in a manner not limited to the scope of the embodiments.
[0051] Example 1
[0052] (1) Drying the NH2-MIL-101(Cr)MOFs material in a vacuum oven at 150°C for 12 h to remove the bound water molecules in the material;
[0053] (2) Weigh 3.2 g of ethanolamine and dissolve it in anhydrous ethanol. Stir it magnetically to make it evenly dispersed. Then add 3.2 g of NH2-MIL-101(Cr) in three portions and stir for 12 hours to allow ethanolamine to fully contact and react with the MOF material. Finally, centrifuge the product and wash it with ethanol several times to remove excess ethanolamine.
[0054] (3) According to the mass ratio of filler: PIM-1 = 0.05:1, the filler and PIM are mixed with chloroform (the total concentration of PIM-1 and filler in CHCl3 solution is 5.5wt%), and the film-forming solution is uniformly dispersed by ultrasonic stirring method;
[0055] (4) The prepared membrane-forming solution is then degassed and transferred to a clean watch glass. The lid is closed to allow the membrane solution to evaporate slowly. After the solvent evaporates, the membrane is taken out of the watch glass and placed in a vacuum oven at 60° C. to dry for 48 hours to obtain a mixed matrix membrane.
[0056] Example 2
[0057] (1) Weigh 3.2 g of diethanolamine and dissolve it in anhydrous ethanol. Stir it magnetically to make it evenly dispersed. Then add 3.2 g of NH2-MIL-101(Fe) without removing bound water in three portions. Stir for 12 h to allow diethanolamine to fully contact and react with NH2-MIL-101(Fe)MOFs material without removing bound water. Finally, centrifuge the product and wash it with ethanol several times to remove excess diethanolamine.
[0058] (2) According to the mass ratio of filler: PIM-1 = 0.1:1, the filler and PIM are mixed with chloroform (the total concentration of PIM-1 and filler in CHCl3 solution is 5.5wt%), and the film-forming solution is uniformly dispersed by ultrasonic stirring method;
[0059] (3) The prepared membrane-forming solution is then degassed and transferred to a clean watch glass. The lid is closed to allow the membrane solution to evaporate slowly. After the solvent evaporates, the membrane is taken out of the watch glass and placed in a vacuum oven at 60° C. to dry for 48 hours to obtain a mixed matrix membrane.
[0060] Example 3
[0061] (1) Weigh 3.2 g of diisopropylamine and dissolve it in anhydrous ethanol. Stir it magnetically to make it evenly dispersed. Then add 3.2 g of NH2-MIL-101(Zn) without removing bound water in 5 portions. Stir for 12 hours to allow diisopropylamine to fully contact and react with NH2-MIL-101(Zn)MOFs material without removing bound water. Finally, centrifuge the product and wash it with ethanol several times to remove excess diisopropylamine.
[0062] (2) According to the mass ratio of filler: PIM-1 = 0.2:1, the filler and PIM are mixed with chloroform (the total concentration of PIM-1 and filler in CHCl3 solution is 5.5wt%), and the film-forming solution is uniformly dispersed by ultrasonic stirring method;
[0063] (3) The prepared membrane-forming solution is then degassed and transferred to a clean watch glass. The lid is closed to allow the membrane solution to evaporate slowly. After the solvent evaporates, the membrane is taken out of the watch glass and placed in a vacuum oven at 60° C. to dry for 48 hours to obtain a mixed matrix membrane.
[0064] Example 4
[0065] The method of Example 1 is followed, except that in step (3), the mass ratio of filler to PIM-1 is 0.1:1, and the other conditions are the same as those of Example 1.
[0066] Example 5
[0067] The method of Example 1 is followed, except that in step (3), the mass ratio of filler to PIM-1 is 0.15:1, and the other conditions are the same as those of Example 1.
[0068] Example 6
[0069] (1) Weigh 3.2 g of ethanolamine and dissolve it in anhydrous ethanol. Stir it magnetically to make it evenly dispersed. Then add 3.2 g of NH2-MIL-101(Cr) without removing bound water in three portions. Stir for 12 hours to allow ethanolamine to fully contact and react with MOF materials. Finally, centrifuge the product and wash it with ethanol several times to remove excess ethanolamine.
[0070] (2) According to the mass ratio of filler: PIM-1 = 0.05:1, the filler and PIM are mixed with chloroform (the total concentration of PIM-1 and filler in CHCl3 solution is 5.5wt%), and the film-forming solution is uniformly dispersed by ultrasonic stirring method;
[0071] (3) The prepared membrane-forming solution is then degassed and transferred to a clean watch glass. The lid is closed to allow the membrane solution to evaporate slowly. After the solvent evaporates, the membrane is taken out of the watch glass and placed in a vacuum oven at 60° C. to dry for 48 hours to obtain a mixed matrix membrane.
[0072] Example 7
[0073] The method of Example 6 is followed, except that in step (2), the mass ratio of filler to PIM-1 is 0.10:1, and the other conditions are the same as those of Example 6.
[0074] Example 8
[0075] The method of Example 6 is followed, except that in step (2), the mass ratio of filler to PIM-1 is 0.10:1, and the other conditions are the same as those of Example 6.
[0076] Test Case
[0077] The performance of the mixed matrix membrane was tested: the membrane sample was pre-humidified and installed in the membrane pool for testing. The raw gas used was CO2 (15% vol) and N2 (85% vol). During the test, the raw gas (and purge gas) was humidified by the humidification tank and then entered the membrane pool. The operating temperature was room temperature (25°C) and the operating pressure was 0.5MPa (G). When the membrane performance was stable, the concentration of the permeate gas (and purge gas) was detected by gas chromatography. The CO2, N2 permeation rate and CO2 / N2 separation factor were calculated using a general calculation formula. The test results are shown in Table 1.
[0078] Table 1
[0079]
[0080] Comparative Example 1
[0081] (1) PIM was mixed with chloroform (the total concentration of PIM-1 and filler in CHCl3 solution was 5.5 wt%), and the mixture was uniformly dispersed by ultrasonic stirring to obtain a film-forming solution;
[0082] (2) The prepared membrane-forming solution was then degassed and transferred to a clean watch glass. The lid was closed to allow the membrane solution to evaporate slowly. After the solvent evaporated, the membrane was taken out of the watch glass and dried in a vacuum oven at 60°C for 48 hours to prepare a PIM-1 membrane. According to the above test method, the CO2 permeation rate was 320 GPU and the CO2 / N2 separation factor was 40.
[0083] Comparative Example 2
[0084] (1) According to the mass ratio of NH2-MIL-101(Cr)MOF material:ethanolamine:PIM-1=0.025:0.025:1, the filler and PIM are mixed with chloroform (the total concentration of PIM-1 and filler in CHCl3 solution is 5.5wt%), and the film-forming solution is uniformly dispersed by ultrasonic stirring method;
[0085] (2) The prepared membrane-forming solution is then degassed and transferred to a clean watch glass. The lid is closed to allow the membrane solution to evaporate slowly. After the solvent evaporates, the membrane is taken out of the watch glass and placed in a vacuum oven at 60° C. to dry for 48 hours to obtain a mixed matrix membrane.
[0086] According to the above test method, the CO2 permeation rate is 505GPU and the CO2 / N2 separation factor is 60.
[0087] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A mixed matrix membrane, characterized in that The mixed matrix membrane includes a polymer matrix and fillers dispersed in the polymer matrix; The filler comprises a MOF material and a MA complex amine loaded on the MOF material; The MA complex amine is selected from one or more of ethanolamine, methyl monoethanolamine, diethanolamine, N-methyl diethanolamine, diisopropylamine, hydroxyethyl ethylenediamine and 2-amino-2-methyl-1-propanol.
2. The mixed matrix membrane according to claim 1, wherein The mass content of the filler is 3-20wt% based on the total weight of the mixed matrix membrane.
3. The mixed matrix membrane according to claim 1 or 2, wherein The MOF material comprises: Metal center; and Organic ligands that hybridize with the bimetallic center through coordination bonds to form a three-dimensional network structure crystal; Preferably, the metal is selected from one or more of iron, copper, zinc, titanium, cobalt, nickel and chromium; The organic ligand is selected from one or more of benzimidazole, imidazole-2-carboxaldehyde, 2-methylimidazole and 2-aminoterephthalic acid.
4. The mixed matrix membrane according to claim 1 or 2, wherein The MOF material is selected from one or more of NH2-MIL-101(Cr), NH2-MIL-101(Fe) and NH2-MIL-101(Zn); and / or In the filler, the mass ratio of MA complex amine to MOFs material is 0.5-1:0.8-2.
5. The mixed matrix membrane according to claim 1 or 2, wherein The preparation method of the filler comprises: The MOF material is contacted with a solution containing MA complex amine, and then separated, washed and dried.
6. The mixed matrix membrane according to claim 5, wherein The MOF material contains bound water or does not contain bound water; preferably, the MOF material contains bound water; The conditions for removing bound water in MOF include: under negative pressure, temperature of 100-180°C, time of 2-24h; The contact time is 3-20h; In the solution containing MA complex amine, the solvent is selected from one or more of anhydrous ethanol, anhydrous methanol and N,N'-dimethylformamide; In the solution containing MA complex amine, the mass ratio of MA complex amine to solvent is 0.2-5:
1.
7. The mixed matrix membrane according to claim 1 or 2, wherein: The polymer matrix is selected from one or more of microporous polymer material PIM-1, cellulose polymer, polysulfone polymer, polyamide polymer, amino polymer, ether oxide polymer, preferably microporous polymer material PIM-1.
8. The method for preparing a mixed matrix membrane according to any one of claims 1 to 7, characterized in that: The method includes: The polymer matrix and filler are dispersed in an organic solvent according to a certain proportion to obtain a membrane-forming liquid, and then the organic solvent in the membrane-forming liquid is removed and dried to obtain a mixed matrix membrane.
9. The preparation method according to claim 8, The organic solvent is selected from one or more of water, tetrahydrofuran, N,N'-dimethylformamide, methanol, ethanol, dichloromethane, and dimethyl sulfoxide; and / or The total weight of the polymer matrix and the filler accounts for 1-15wt% of the membrane-forming solution; and / or Drying conditions include: Negative pressure, temperature 60-150℃, time 2-24h.
10. Use of the mixed matrix membrane according to any one of claims 1 to 7 in CO2 membrane separation, preferably in CO2 / N2 membrane separation.
Citation Information
Patent Citations
Intrinsic microporosity / amino modified metal-organic framework (MOF) mixed matrix membrane, and preparation method and application thereof
CN110559890A
Amino metal organic framework adsorbent capable of adsorbing carbon dioxide in air as well as preparation and application of amino metal organic framework adsorbent
CN114849665A